Flavonol glycosides from Dasymaschalon sootepense - Andrea Sinz (2018)
Two novel flavonol glycosides have been isolated from a methanolic extract of Dasymaschalon sootepense leaves. They are the 3'-neohesperidoside and 3'(6(G)-α-rhamnosylneohesperidoside) of quercetin 3,7-dimethyl ether.